SZAP exerts analgesic effects on rheumatalgia in CIA rats by suppressing pain hyperalgesia and inhibiting TRPV1 and P2X3. (10th February 2022) - Wang, Jie; Wen, Wen; Gong, Daoyin; Chen, Qi; Li, Ping; Liu, Panwang; Wang, Fushun; Xu, Shijun
Abstract: Ethnopharmacological relevance: ShexiangZhuifeng Analgesic Plaster (SZAP) is a traditional Chinese medicine and transdermal formulation composed of many Chinese herbs and active compounds. SZAP was recently approved by the China Food and Drug Administration for the treatment of pain associated with osteoarticular diseases and is preferred by most rheumatoid arthritis patients in China. However, its mechanism has not been elucidated in detail. Aim of the study: We sought to determine the analgesic effect of SZAP in collagen-induced arthritis (CIA) rats and explore the underlying mechanisms of pain transmission, such as via the TRPV1 and P2X3 receptors. Methods: After CIA was established, rats were treated with SZAP for 7 days. Paw thickness, arthritis score, and haematoxylin and eosin staining were used to evaluate the effectiveness of SZAP. Paw withdrawal threshold (PWT) and tail-flick latency (TFL) were used to estimate the analgesic effect of SZAP. The levels of PGE2, BK, 5-HT, SP, and CGRP in the serum and synovium were determined using ELISA kits, and ATP in the synovium was measured using HPLC. The expression of TRPV1 and P2X3 in the DRG was detected using western blotting and immunofluorescence. TRPV1 and P2X3 agonists were further used to determine the analgesic effects of SZAP on CIA rats based on PWT and TFL. Results: SZAP not only significantly ameliorated arthritis scores and paw thickness by improving the pathological damage of synovial joints, but also remarkably alleviated pain in CIA rats. Further, treatment with SZAP significantly reduced peripheral 5-HT, PGE2 BK, SP, CGRP, and ATP. Additionally, the expression of TRPV1 and P2X3 in the DRG was markedly downregulated by SZAP. Interestingly, the analgesic effect of SZAP was weakened (reduction of PWT and TFL) when TRPV1 and P2X3 were activated by capsaicin or α, β-meATP, respectively. Conclusion: SZAP ameliorates rheumatalgia by suppressing hyperalgesia and pain transmission through the inhibition of TRPV1 and P2X3 in the DRG of CIA rats. Graphical abstract: Image 1